Titling community land to prevent deforestation: An evaluation of a best-case program in Morona-Santiago, Ecuador. (July 2015) - Buntaine, Mark T.; Hamilton, Stuart E.; Millones, Marco
Highlights: Given their global reach, better evidence about land titling programs is critical. Land titling and community management programs did not reduce deforestation. Careful matching of program and non-program areas produces more reliable estimates of program impacts. Remote sensing data is a key tool for evaluating the impacts of globally relevant policies. Abstract: Assigning land title to collective landholders is one of the primary policies land management agencies use to avoid deforestation worldwide. Such programs are designed to improve the ability of landholders to legally exclude competing users and thereby strengthen incentives to manage forests for long-term benefits. Despite the prevalence of this hypothesis, findings about the impacts of land titling programs on deforestation are mixed. Evidence is often unreliable because programs are targeted according to factors that independently influence the conversion of forests. We evaluate a donor-funded land titling and land management program for indigenous communities implemented in Morona-Santiago, Ecuador. This program offers a close to best case scenario for a land titling program to reduce deforestation because of colonization pressure, availability of payments when titled communities maintain forests, and limited opportunities for commercial agriculture. We match plots in program areas with similar plots outside program areas on covariates that influence the conversion of forests. Based on matched comparisons, we do not find evidence that land titling or community management plans reduced forest loss in the five years following legal recognition. The results call into question land titling as a direct deforestation strategy and suggests land titling is better viewed a precursor to other programs.